2010
DOI: 10.1063/1.3465120
|View full text |Cite
|
Sign up to set email alerts
|

Achieving optical gain in waveguide-confined nanocluster-sensitized erbium by pulsed excitation

Abstract: We use a rate equation approach to model the conditions for optical gain in nanocluster sensitized erbium in a slot waveguide geometry. We determine the viability of achieving net gain for the range of reported values of the carrier absorption cross section for silicon nanoclusters. After accounting for the local density of optical states modification of the emission rates, we find that gain is impossible in continuous wave pumping due to carrier absorption, regardless of the carrier absorption cross section. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the previously mentioned simulation by Miller et al [26], a 10 nm Er:Si-ncs layer (in SiO 2 ) slot waveguide sandwiched between two Si layers is proposed to obtain modal gain under a pulsed injection scheme. The study shows that modal gain can be enhanced from <1 dB/cm to 2-3 dB/cm when the thickness of active layer is increased from 10 nm to 50 nm.…”
Section: Trade-off Between Sample Thickness and Si Excess To Optimizementioning
confidence: 99%
See 1 more Smart Citation
“…In the previously mentioned simulation by Miller et al [26], a 10 nm Er:Si-ncs layer (in SiO 2 ) slot waveguide sandwiched between two Si layers is proposed to obtain modal gain under a pulsed injection scheme. The study shows that modal gain can be enhanced from <1 dB/cm to 2-3 dB/cm when the thickness of active layer is increased from 10 nm to 50 nm.…”
Section: Trade-off Between Sample Thickness and Si Excess To Optimizementioning
confidence: 99%
“…However, no net optical gain has yet been reported for electrically-driven SiO x :Er devices, and the state-of-the-art highest fraction of electrically excited Er 3+ ions is 20% [25]. Nevertheless, two recent simulation works showed that (i) it is theoretically possible to achieve modal gain via pulsed electrical excitation of waveguide-confined devices [26], and (ii) light can be efficiently coupled from electrically-pumped SiO x :Er into silicon waveguides [27]. Such results are promising for future all-silicon optical-circuitry and highlight the need to better understand the physics of carrier transport and erbium excitation in fabricated devices.…”
Section: Introductionmentioning
confidence: 99%
“…11 Miller et al calculated a modal gain of 2 dB/cm in a slot waveguide confined Si-NC:Er under the pulsed excitation which mitigates excited carrier absorption. 12 In this work, we will evaluate erbium excitation mechanisms and emission in Si-NC:Er LED under electrical pumping using both direct current and bipolar pulsed excitation schemes, i.e., when the polarity of the applied voltage pulse is periodically changed.…”
Section: Introductionmentioning
confidence: 99%
“…Also, much attention has been paid to carrier absorption (CA) losses at 1.53 μm in Si-nanocrystal (Si-ncs) waveguides by means of optical pumping [12], determining an accurate characterization of the optical losses even in slot waveguides [13]. Still, the possible performance of this geometry in an electrical pump & probe scenario have only been modeled [14], but never studied experimentally.…”
Section: Introductionmentioning
confidence: 99%